Efforts to Increase the Learning Activity of Class VIII B Students of SMPN 17 Mataram in Pancasila Education Learning Through the Application of the Role Playing Method. - pandriani, _halimatu; Sumardi, Lalu; Sawaludin, Sawaludin (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This study aims to improve the learning activity of class VIII B students of SMP Negeri 17 Mataram in the Pancasila Education subject through the application of the role playing learning method. This type of research is Classroom Action Research (CAR) which is carried out in three cycles, where each cycle consists of the planning, implementation, observation, and reflection stages. The subjects of the study were 45 class VIII B students of SMP Negeri 17 Mataram in the even semester of the 2025/2026 academic year. Data were collected through observation, questionnaires, and documentation, then analyzed descriptively qualitatively and quantitatively. The results of the study showed that the application of the role playing method was able to significantly increase student learning activity in each cycle. The percentage of student learning activity in cycle I was 69.42% (good category), increased to 86.77% (very good category) in cycle II, and reached 93.33% (very good category) in cycle III. This increase was seen in the aspect of student courage in asking questions, expressing opinions, working together in groups, and performing in front of the class. Thus, the application of the role playing method has proven effective in creating an active, interactive, and enjoyable learning atmosphere, thereby increasing students' learning activity in the Pancasila Education subject.